The Role of the State in Assuring the Fairness of Distribution in Vietnam Today: Some Issues - Vinh, Le Thi (VNU Journal of Science: Policy and Management Studies; Vol 34 No 2DO - 10.25073/2588-1116/vnupam.4140, 2018)
The paper analyzes the issues arisen from the implementation of the State’s role in assuring the fairness of distribution through a philosophical approach. First, the paper analyzes the shortcomings of the State in ensuring equitable distribution, namely the State's unreasonable interference in the distribution relations, its failure to properly implement the planning, inspecting and supervising tasks in the implementation of the distribution policies. Second, the paper discusses the consequence resulted from the State’s improper implementation of the management, regulation and distribution roles; specifically, the gap between the rich and the poor is widening and polarizing, threatening social stability and development. Third, the paper proposes some principles for the State to consider for inplemeting to further assure fair distribution. Keywords: The role of the State, the distribution relations, fair distribution.